Uso de herramientas digitales y el aprendizaje del área de ciencias sociales en los estudiantes de secundaria de la I.E.P.S.M TNTE. Manuel Clavero Muga 2025 - Lozano Castillo, Kriss Alexandra (2025)
The purpose of this research was to determine how the use of digital tools relates to social science learning among secondary school students at the Institución Educativa Primaria Secundaria Mixto Teniente Manuel Clavero Muga, 2025. The research was basic, quantitative, correlational, and non-experimental in design, with a cross-sectional sample of 65 students. The findings show that a large proportion of students (46.1%) indicate low use of digital tools, 38.5% indicate medium use of these tools, while 15.4% report high use. In terms of learning in the area of social sciences, 49.2% of students achieved a medium level, 27.7% a low level, and 23.1% a high level. Using Spearman's Rho test, a high positive correlation was determined (rho=0.485; p= 0.000<0.05), concluding that the use of digital tools is significantly related to learning in the area of Social Sciences.